Ethnobotany of Anti-hypertensive Plants Used in Northern Pakistan - Malik, Khafsa; Ahmad, Mushtaq; Bussmann, Rainer W.; Tariq, Akash; Ullah, Riaz; Alqahtani, Ali S.; Shahat, Abdelaaty A.; Rashid, Neelam; Zafar, Muhammad; Sultana, Shazia; Shah, Syed N. (Frontiers in Pharmacology, 2018)
Ethnobotanty of Hypertensive plants used in Northern areas of Pakistan